Islam and Interfaith Dialogue: Some Observations (American Journal of Islam and Society, 2014)
On March 21, 2014, Seyed Amir Akrami, a visiting Iranian scholar at the EasternMennonite University in Harrisonburg, VA, visited the headquarters ofthe International Institute of Islamic Thought. He holds a PhD in the philosophyof religion (McGill University), as well as a BA and an MA in Islamictheology and mysticism (University of Tehran).In his opening remarks he stated that with the end of the Cold War, thecloser relations between politics and religion necessitates interfaith relations.Realizing this, the West (especially the United States) has undertaken an unprecedentedstep: establishing centers for religion and diplomacy. Akrami considersthis a very positive development. Another reason for this new approachwas Samuel Huntington’s (d. 2008) “clash of civilizations” theory, which upsetmany Muslims. What is often forgotten, however, is that Huntington alsocalled for dialogue. President Mohammad Khatami of Iran responded to thisby launching his 2001 “dialogue of civilizations” initiative. Akrami maintainsthat political and economic polarization is being replaced by cultures, of whichreligion is a very important part. Given that Islam and Christianity are theworld’s two largest religions, it is more practical to focus on them than tryingto start a dialogue with all religions at this time.The second part of his presentation consisted of several historical observationsrelated to Christian views of Islam, Muslim views of other religions(especially Christianity), and how best to approach/view these two religions’relationship. John of Damascus (d. 750), an early Christian scholar of Islamnoted for his largely polemical works, viewed Islam as a Christian heresy.Centuries later, the Crusades poisoned Muslim-Christian relations. But, importantly,part of the reason for this military onslaught was the great schismof 1054 that split Christendom between the Catholic Church (Rome) and theOrthodox Church (Constantinople).Normal Daniel’s Islam and the West: The Making of an Image (Oxford:Oneworld, 1993) is a very good source for these negative views. Among themare the following: (1) Muhammad was a cardinal who wanted to become thepope. When he failed in this attempt, he became a heretic; (2) Muhammadtrained a dove or a bird to sit on his shoulder in order to deceive/delude hisfollowers into thinking that he was being inspired; and (3) Dante, in his DivineComedy, called Muhammad an imposter and liar and therefore placed him inthe eighth circle of hell ...